7x-6=-2x+3

Simple and best practice solution for 7x-6=-2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-6=-2x+3 equation:


Simplifying
7x + -6 = -2x + 3

Reorder the terms:
-6 + 7x = -2x + 3

Reorder the terms:
-6 + 7x = 3 + -2x

Solving
-6 + 7x = 3 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-6 + 7x + 2x = 3 + -2x + 2x

Combine like terms: 7x + 2x = 9x
-6 + 9x = 3 + -2x + 2x

Combine like terms: -2x + 2x = 0
-6 + 9x = 3 + 0
-6 + 9x = 3

Add '6' to each side of the equation.
-6 + 6 + 9x = 3 + 6

Combine like terms: -6 + 6 = 0
0 + 9x = 3 + 6
9x = 3 + 6

Combine like terms: 3 + 6 = 9
9x = 9

Divide each side by '9'.
x = 1

Simplifying
x = 1

See similar equations:

| 9-5x^2=-71 | | 11x+2=14x-7 | | y=2x+1(X) | | 2(2x-4)=-20 | | 94.9536=20.3472+11.304h | | 15-(-42)= | | 880=2n^2-4n | | 1672.992=2*3.14*r^2+2*3.14*7.2*h | | 5(x+7)-6(x+6)=0 | | N^2=8n-16 | | t=2m(m) | | 3(5)+7(-6)= | | 1x-3=3x-13 | | y-6=2y-15 | | -5(-3p-4)=-70 | | 5-4(x-2)=12x-3 | | 24=2(v+2)+2v | | 2x+(-6)=3(2x-10) | | b^2+6b=-5 | | 8.1x-3.7=2.4x+2 | | 5x+16=5-5 | | 3(2-5m)=81 | | (-3+6i)(1+i)= | | P-19=34 | | -38=3(y-6)+2y | | 4x-7=4(x-3)+5 | | 8/n=12/15 | | 16x-7=13x+2 | | -38=8(y-6)+2y | | -4(6x+1)+6x=68 | | x=15-3x | | 2x^2+2y^2=10 |

Equations solver categories